2020
DOI: 10.1186/s11671-020-03357-2
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Long Non-coding RNA MALAT1/microRNA-143/VEGFA Signal Axis Modulates Vascular Endothelial Injury-Induced Intracranial Aneurysm

Abstract: The roles of some long non-coding RNAs (lncRNAs) in intracranial aneurysm (IA) have been investigated in many studies. The aim of this study is to elucidate the mechanism of lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1)/microRNA-143 (miR-143)/vascular endothelial growth factor-A (VEGFA) signal axis in vascular endothelial injury-induced IA. MALAT1, miR-143, and VEGFA expression in IA tissues and normal arterial tissues were detected. Matrix metalloproteinase 9 (MMP-9) in tissues, von W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…In addition, it has previously been discussed that cluster miR-143/miR-145 takes part in various biological processes associated with IA formation and the expression cluster miR-143/miR-145 is downregulated in IA tissues [65]. Gao et al in their study showed that lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) and VEGF-A are upregulated and miR-143 is downregulated in IA tissues (rat models of IA and IA patients) [66]. Moreover, the authors demonstrated that a decrease in MALAT1 expression induced by short hairpin RNA (sh)-MALAT1 interference inhibited apoptosis and promoted the viability of ECs in IA by modulating miR-143/VEGF-A axis.…”
Section: Lncrna-based Therapeuticsmentioning
confidence: 99%
“…In addition, it has previously been discussed that cluster miR-143/miR-145 takes part in various biological processes associated with IA formation and the expression cluster miR-143/miR-145 is downregulated in IA tissues [65]. Gao et al in their study showed that lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) and VEGF-A are upregulated and miR-143 is downregulated in IA tissues (rat models of IA and IA patients) [66]. Moreover, the authors demonstrated that a decrease in MALAT1 expression induced by short hairpin RNA (sh)-MALAT1 interference inhibited apoptosis and promoted the viability of ECs in IA by modulating miR-143/VEGF-A axis.…”
Section: Lncrna-based Therapeuticsmentioning
confidence: 99%
“…Endothelial cells are the main cell type of blood vessels and involved in the process of vascular morphogenesis, homeostasis and diseases [6]. Endothelial cell injury resulted by in ammation has been reported to be involved in the development of diseases, including atherosclerosis, cerebral aneurysm and IAs [7][8][9]. In addition, increasing studies have demonstrated that endothelial cell senescence and functional alterations also play important roles in vascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“… 10 For instance, lncRNAs and miRNAs affect protein production and regulate other noncoding RNAs to regulate IA growth and rupture. 11 , 12 Although lacking protein-coding capacity, lncRNAs and miRNAs participate in human diseases, including IA, mainly by affecting the expression of protein-coding genes. Therefore, regulating the expression of certain miRNAs or lncRNAs with critical functions in IA may provide potentials for IA treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, regulating the expression of certain miRNAs or lncRNAs with critical functions in IA may provide potentials for IA treatment. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation